RP-HPLC Method Development and Validation for the Simultaneous Estimation of Metoprolol and Telmisartan in Tablet Dosage Form - K.Pranitha; Tabassum; J.Priya; N.Ramathilagam (International Journal of Pharmacy and Analytical Research, 2014)
A simple reversed-phase high-performance liquid chromatographic (RP-HPLC) method has been developed and validated for simultaneous determination of Metoprolol and Telmisartan in pharmaceutical tablet dosage form. Chromatographic analysis was performed on a Symmetry X-terra C8 (4.6 mm x 100 mm, 5 m) column at ambient temperature with a mixture of ortho phosphoric acid buffer and Acetonitrile, Methanol in the ratio 45:10:45 v/v as mobile phase, at a flow rate of 0.7 mL min-1 . UV detection was performed at 226 nm. The retention times of Metoprolol and Telmisartan were 2.473 and 3.407 min, respectively. The correlation coefficient of Metoprolol and Telmisartan was found to be 0.999. Calibration plots were linear over the concentration ranges 12.5–62.5 μg mL-1 and 10-50 μg mL-1 for Metoprolol and Telmisartan, respectively. The Limit of detection was 0.667 and 0.846µg mL-1 and the quantification limit was 2.021 µg mL-1 and 2.565 µg mL-1 for Metoprolol and Telmisartan, respectively. The accuracy of the proposed method was determined by recovery studies and found to be 99.93% to 101.09%.The method was validated for accuracy, linearity, sensitivity, precision, robustness, system suitability Commercial tablet formulation was successfully analyzed using the developed method and the proposed method is applicable to routine analysis of determination of Metoprolol and Telmisartan in pharmaceutical tablet dosage form.